Pulmonary Artery Pseudoaneurysm with Recurrent Massive Haemoptysis: Endovascular Management by a Covered Stent - Choh, Naseer A.; Amreen, Saika; Hamid, Mudasir; Nazir, Imran (Journal of Clinical Interventional Radiology ISVIR, 2021)
Pulmonary artery pseudoaneurysm (PAPA) is a potentially fatal, albeit rare cause of hemoptysis. With a varied etiology and debatable management, time is the essence in its treatment. We present a case of a post lobectomy PAPA with recurrence of malignancy, managed via endovascular approach in a low resource setting where an ideal hardware was not available.
Keywords: pulmonary artery pseudoaneurysm; covered stent; thrombin